Meningkatkan Promosi Penjualan Melalui Pemanfaatan Aplikasi Canva pada Pelaku UMKM di Kelurahan Sambiroto, Kecamatan Tembalang, Kota Semarang - Sutopo Sutopo; Haryani Haryani; Alfin Muslikhun; Ceria May Diana (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
MSMEs have an important role in the Indonesian economy, but many have difficulty in effective digital promotion. The Canva application offers a practical solution for MSME players in creating attractive and professional visual content without requiring special design skills. This community service activity aims to train MSME players in Sambiroto Village, Tembalang, to utilize the Canva application as a promotional tool to increase sales. This training includes an introduction to Canva features, the use of templates, and basic design techniques that support product branding and marketing. The results showed that the training participants successfully understood and applied Canva in creating effective promotional content, increasing the visual appeal of products on social media. This increased understanding is expected to help MSME players expand their market and significantly increase the competitiveness of their products.